Pedro Costa: producing and consuming contemporary art cinema - Barradas Jorge, Nuno (2016)
This thesis examines the work of Portuguese filmmaker Pedro Costa as a paradigm of recent developments in production and consumption practices in contemporary art cinema. With a notable problematic relationship with industrial film production and with a pragmatic approach to distribution, Costa’s working methods have sustained an evolving narrative of production that negotiates between interstitial filmmaking, and different authorial and collaborative practices, which helped his work to circulate in different circuits of consumption. Scholarly study of Costa’s work has stressed particular stylistic tropes within his films, yet little attention has been given to the authoring processes and production contexts of his oeuvre, or to the mediating factors that impact on his work’s multifaceted exhibition and circulation. These practices come to impact, to considerable extent, in Costa’s filmic style, and to define his agency as a filmmaker – both as a creative practitioner and a linking agent in different fields of production and circulation. This study emphasises the importance of Costa’s agency as a salient factor in the negotiations shaping contemporary art cinema. It maps the cultural, industrial and economic contexts from which the Costa’s working practices emerged, and how these contexts formed a production blueprint that came to support both the production and consumption of his films.